Infrared Radiofluorescence (IR-RF) of K-Feldspar: an interlaboratory comparison - Murari, Madhav Krishna; Kreutzer, Sebastian; Frouin, Marine; Friedrich, Johannes; Lauer, Tobias; Klasen, Nicole; Schmidt, Christoph; Tsukamoto, Sumiko; Richter, Daniel; Mercier, Norbert; Fuchs, Markus (Geochronometria, 2021)
Infrared Radiofluorescence (IR-RF) is a relatively new method for dosimetric dating of the depositional timing of sediments. This contribution presents an interlaboratory comparison of IR-RF measurements of sedimentary feldspar from eight laboratories. A comparison of the variability of...
Gesehen am 27.03.2025